2005
DOI: 10.1007/s00066-005-1418-3
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of the Hemoglobin Solution HBOC-201 on the Response of the Rat R1H Tumor to Fractionated Irradiation

Abstract: Low-dose application of HBOC-201 does not improve the response of the rhabdomyosarcoma R1H of the rat to fractionated irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Details of this tumor system have been reported previously [13,17,22]. Cryoconserved stock tumors were serially passaged subcutaneously into the back (laterally, subcostally) of syngenic WAG/Rij albino rats.…”
Section: Tumor Host Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of this tumor system have been reported previously [13,17,22]. Cryoconserved stock tumors were serially passaged subcutaneously into the back (laterally, subcostally) of syngenic WAG/Rij albino rats.…”
Section: Tumor Host Systemmentioning
confidence: 99%
“…Cryoconserved stock tumors were serially passaged subcutaneously into the back (laterally, subcostally) of syngenic WAG/Rij albino rats. For details of the transplantation procedure and tumor maintenance see [13,17,18,22,24]. Animals were housed under conventional conditions and were provided with food and water ad libitum.…”
Section: Tumor Host Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, moderate tumor oxygenation potential was observed with high affinity HBOCs in a study conducted in 1998 [ 23 ]. A 2005 study demonstrated that low O 2 affinity PolyhHb oxygenated a rhabdomyosarcoma to a lesser extent than carbogen-based therapies [ 24 ]. In contrast, a 2008 computational simulation indicated that HBOCs with reduced O 2 affinities may selectively oxygenate hypoxic tissue [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…PbtO2 monitoring has also been used in animal models of spontaneous intracerebral hemorrhage [110,156], malignant soft tissue tumors [157,158], ischemic stroke [159], in experimental subarachnoid hemorrhage [160], in a swine model of pediatric traumatic brain injury [161], a rodent model of penetrating ballistic-like brain injury [162], in a rodent model of acclimation and deacclimation to hypoxia [163], in a standardized experimental brain death model [164], in experimental anhepatic liver failure [165,166], an in potassium-induced cortical spreading depression [167].…”
Section: Animalmentioning
confidence: 99%